Metformin/Glimepiride and Metformin/Glibenclamide, Which is Better?: A Systematic Review and Meta-Analysis - Sukmawan, Yedy Purwandi (Indonesian Journal of Medicine, 2019)
Background: Type 2 diabetes mellitus (DM) is associated with the microvascular and macrovascular complication. Metformin and sulphonylurea (glimepiride and glibenclamide) combination is widely used for the treatment of type 2 DM. This study aimed to examine the difference of Metformin/Glimepiride and Metformin/Glibenclamide administrations in reducing HbA1C among type 2 DM patients.Subjects and Method: This was a systematic review and meta-analysis according to PRISMA guideline with PICO construction using MeSH and text-word. 214 article were identified from PubMed, Cochrane, other source databases. Two articles with 183 type 2 DM  patients were selected for this study.Results: No significant difference on HbA1C level, fasting plasma glucose, and hypoglycemia adverse events between glimepiride/metformin and glibenclamide/metformin combinations. However, glimepiride/metformin combination demonstrated lower HbA1C (-0.11; 95% CI= -0.41 to 0.18; p= 0.450) and lower hypoglycemia adverse events (OR= 0.52; 95% CI= -1.02 to 3.05; p= 0.450), while glibenclamide/metformin combination demonstrated lower fasting plasma glucose concentration (1.01; 95% CI= -1.02 to 3.05; p= 0.450).Conclusion: Glimepiride/metformin combination is preferable in HbA1C lowering and hypoglycemia risk than glibenclamide/metformin combination.Keywords: Glimepiride-metformin, Glibenclamide-metformin, type 2 diabetes mellitusCorrespondence: Yedy Purwandi Sukmawan. Department of Clinical Pharmacy and Pharmacology, Institute of Health Science of Bakti Tunas Husada Tasikmalaya, West Java, Indonesia. Email: yedipur@gmail.comIndonesian Journal of Medicine (2019), 4(3): 211-218https://doi.org/10.26911/theijmed.2019.04.03.03